PKM Pemberdayaan Warga Binaan Di Lapas Perempuan Klas II B Bengkulu - Imanda, Antonio; Handayani, Tuti; Sariningsih, Marida; Rikardo, Yanuar; Yusuarsono, Yusuarsono; Nova, Nova; Larasati, Jesicha Fitria (Jurnal Dehasen Untuk Negeri, 2024)
This Community Service (PKM) activity aims to empower inmates at the Class II B Women's Correctional Institution (Lapas) in Bengkulu through interpersonal communication training, personality development, and independence. This program is motivated by the importance of increasing the social and psychological capacity of inmates so they can adapt positively, build self-confidence, and prepare themselves for social reintegration after the rehabilitation period ends. The implementation method of the activity uses an educational, participatory, and humanistic approach, which emphasizes the active involvement of participants in the training process through interactive lectures, group discussions, communication simulations, and self-reflection. The activity was attended by 40 female inmates and facilitated by a team of lecturers and students from Dehasen University Bengkulu in collaboration with the Prison. The results of the activity showed an increase in the inmates' ability to understand and apply the principles of effective interpersonal communication, such as active listening, managing emotions, and conveying messages empathetically. Participants also showed increased self-awareness, self-confidence, and motivation to improve themselves and build more harmonious social relationships. The evaluation of the activity showed that more than 90% of participants felt this activity was very useful and relevant to their needs during the rehabilitation period. This activity demonstrates the effectiveness of a communication-based and psychosocial empowerment approach in strengthening the character, personality, and independence of inmates. The program also emphasizes the crucial role of higher education institutions in supporting a humane and sustainable social rehabilitation process through synergy between academia and correctional institutions.